A Note on Neutrosophic Soft Set over Hyperalgebras - Onar, Serkan (MDPI, 2024)
This research aims to introduce and explore the theory of neutrosophic soft hyperalgebras (NSHAs), focusing on their core principles and potential applications in decision-making under uncertainty. By defining key operations such as intersection and union, we clarify the foundational characteristics of NSHAs and their relationship to soft hyperalgebras. The concepts of xi beta-identity NSHA and xi-absolute NSHA are also examined to better understand their properties. The practical relevance of NSHA is demonstrated through applications in various fields, highlighting its adaptability in addressing complex decision-making scenarios. This approach offers a novel, more precise method for navigating uncertainty in areas such as project methodology selection, sensitivity analysis, and AI chatbot selection.
Keywords: algebraic hyperstructure; homomorphism; hyperalgebra; soft set; neutrosophic soft set; MATRIX-THEORY; DECISION; SIMILARITY; Science & Technology - Other Topics